Peroxidase isoenzyme patterns of resistant and susceptible wheat leaves following stem rust infection - Flott, Berenike E (The New phytologist, 1989)
Near-isogenic lines of the wheat (Triticum aestivum L.) cultivar Prelude, currying either the sr5 gene for susceptibility or the Sr5 allele for resistance to stem rust (Puccinia graminis Pers. f. sp. tritici Erics. & E. Henn.) were inoculated with race 32 of the fungus which possesses the P5 gene for avirulence. Enzyme extracts prepared at different times after inoculation were separated by non-denaturing gel electrophoresis and the gels were stained for peroxidase activity using different substrates. Both anodic and cathodic gels were run. In anodic separations, resistant and susceptible plants initially both exhibited decreases in the activity of two isoenzymes of low molecular mass, increases in two enzymes of intermediate molecular mass, and induction of two low high molecular mass isoperoxidases. In susceptible plants, these changes proceeded until 3 days after inoculation, when a general decrease in all isoenzymes was observed until 8 days after inoculation. In contrast, in resistant plants, the increases continued up to 7 days after inoculation. In addition, one isoperoxidase appeared about 2-3 days after inoculation only in the incompatible interaction. Cathodic separations revealed that basic isoperoxidases increased after inoculation as well. In the group of small basic isoenzymes, two new bands appeared following inoculation. Only slight differences were seen between the two isolines. Injecting an elicitor isolated from germinated urediniospores into the intercellular spaces of wheat leaves induces typical symptoms of the resistant reaction in both isolines. Correspondingly, the isoperoxidase pattern of the incompatible interaction, including the resistance related isoenzyme, was induced in both isolines. The results are compared with previously reported changes in enzyme activities of the lignin biosynthetic Pathway, including the total activity of peroxidase. The relationship of different isoenzymes to the lignification response as a decisive mechanism of the hypersensitive resistant reaction is discussed